Pengaruh Lingkungan Tempat Tinggal Siswa Terhadap Prestasi Belajar Fisika - Helga C.A. Silubun; Geodita Kame; Ivylentine Datu Palittin (Musamus Journal of Science Education, 2020)
This study aims to determine whether there is an influence of the student's living environment on physics learning achievement of class XI IPA students of YPPK Yos Sudarso High School Merauke in the 2018/2019 school year. This research is a type of quantitative research. The research subjects were class XI IPA students at YPPK Yos Sudarso High School Merauke. The sampling technique uses total sampling. Data collection techniques used were questionnaires to determine the influence of the environment and learning achievement seen from the value of students' report cards. Descriptive and inferential statistics analysis, which includes calculating correlation, normality test, t test and hypothesis test. The results obtained by the hypothesis test sig value. equal to 0.00 with a level of sig 0.05 (0.00 5 0.05), then Ho is accepted and Ha is rejected. So that it can be concluded that there is a significant effect on the student's living environment towards the physics learning achievement of students at YPPK Yos Sudarso High School Merauke.